Is it still "cycling"? Pedelec-commuting from a social-practice-perspective - Paul R. Schneider (Wuppertal Institut für Klima, Umwelt, Energie, 2022)
The sales of pedelecs are currently skyrocketing in Germany and in many other places. As a low-carbon means of mobility, pedelecs have the potential to make a substantial contribution to the mobility transition. This thesis employs practice theory as proposed by Shove et al. (2012) to investigate this quickly evolving phenomenon. The analysis is based on interviews with e-bike commuters which were investigated using template analysis and exploratory memos. To obtain a broad picture the practice, a maximum variance sampling strategy was carried out in two cities that vary substantially with regard to velomobility: Wuppertal and Münster. This thesis one hand presents the first encompassing account on the practice elements which commuting by pedelec is composed of. It hence contributes to the debate about the depiction of practices. Furthermore, the thesis finds that pedelec commuting should be conceptualized as a variant of velomobility and not as a variant of motoring or as an independent practice. Yet, the elements integrated in pedelec-commuting are found to clearly differ from those of cycling, so that pedelec-commuting meets the requirements of everyday life much better than commuting on non-electrified bikes. The findings of this thesis suggest several pathways to strengthening this novel practice. The capacity of e-biking to serve mundane trips can for example be supported through the normalization of the use of weather- and transport relevant materials and competences. Deeper linkages with interacting practices from other sectors, such as an integration of cycling materials (GPS-trackers) into policing practices, can also contribute to this goal. With regard to research, the present work offers starting points for quantifications, for example on the relative importance of single elements as well as on the characteristics of their relations among each other or with regard to typical constellations of elements.
urn:nbn:de:bsz:wup4-opus-80906
Keywords: 330